Perception of parental acceptance-rejection and some personality variables in young adults - Kuterovac-Jagodić, Gordana; Keresteš, Gordana (1997)
The aim of the study was to examine the relationship between Rohner's dimensions of parental behaviour, as retrospectively perceived by young adults, and some personality variables that are postulated to be associated with them. 130 female and 94 male students of the University of Zagreb participated in the study. Mean age of the sample was 21 years. Parental behaviour of both mothers and fathers was assessed by the 32 -items version of Rohner's Adult Parental Acceptance Rejection Questionnaire that asks adults to reflect on the way they were treated when they were at the age of about 7 to 12 years old. The subjects assessed parental behaviour in terms of four dimensions: perceived warmth and affection, perceived hostility and aggression, perceived indifference and neglect and perceived undifferentiated rejection. Personality variables examined were aggression, extroversion and neuroticism and self-esteem. Stepwise regression analysis was performed for each of the personality variables with eight dimensions of perceived parental behaviour of mothers and fathers as predictors. The obtained multiple regression coefficients for the total sample were all significant, although quite low (ranging from .17 to .30). The most predictive variable was the dimension of father's undifferentiated rejection that predicted total aggression score, manifest and latent physical aggression, indirect aggression, verbal latent aggression and neuroticism. Father's warmth and affection predicted extroversion, while father's hostility and aggression was predictive for manifest verbal aggression. Separate analyses performed for the gender subsamples revealed that parental behaviour accounted for more of the variance in personality variables of males than of females. In addition mother's behaviour was shown to be predictive only in the male subsample.
Projekt MZOS
ENG